Histological Changes in Targeted Organs of Nile Tilapia (Oreochromis niloticus) Exposed to Sublethal Concentrations of the Pesticide Carbofuran - Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Machado, Angela Aparecida [UNESP]; da Cruz, Claudinei; Aguiar, Mario Mamede; Ferreira, Luiz Fernando Romanholo; Torres, Nádia Hortense; Machado-Neto, Joaquim Gonçalves [UNESP] (Springer Nature, 2020)
This study aimed to evaluate histological changes in targeted tilapia organs exposed to sublethal concentrations of carbofuran. Fishes with an average weight of 67.5 ± 2.0 g were exposed to sublethal concentrations (0.0044, 0.0088, 0.0440, and 0.0880 mg L−1) of carbofuran for 7 days. In the end of the experiment, the gill, the liver, and the kidney samples were collected for histological evaluation. In gills exposed to 0.0044 mg L−1 of carbofuran, an increase in interlayer epithelium and disruption of the secondary lamella was observed, while in other concentrations (0.0088, 0.0440, and 0.0880 mg L−1), only blood congestion in the secondary lamellae occurred. In the liver samples of exposed tilapias, all carbofuran concentrations caused hepatocyte hypertrophy with the nuclei displaced to the cell periphery, stasis within the sinusoid capillaries, and necrosis points. All sublethal concentrations tested caused detachment of the glomerular capsule, necrosis in the proximal and distal tubules, and absence of intercellular space in the kidney of exposed tilapia. The presence of carbofuran in aquatic environments at concentrations from 0.0044 mg L−1 and exposure periods longer than 7 days alters the gill, the liver, and the kidney histology and consequently compromising the fish’s health.
Keywords: Carbamate; Fish; Necrosis; Toxicity